The Protective Role of Klotho in CKD-Associated Cardiovascular Disease - Xianjin Bi; Ke Yang; Bo Zhang; Jinghong Zhao (Karger Publishers, 2020)
Background: Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality in advanced CKD. The major pathological changes of CKD-associated CVD are severe vascular media calcification, aberrant cardiac remodeling such as hypertrophy and fibrosis, as well as accelerated atherosclerosis. α-Klotho is proposed as an anti-aging gene, which is primarily expressed in the kidney. Recent studies reveal that α-Klotho deficiency is associated with profound cardiovascular dysfunction. Of note, CKD represents extremely declined α-Klotho levels, hinting that α-Klotho deficiency may be implicated in the pathogenesis of CKD-associated CVD. Summary: Based on the pathogenic mechanism of α-Klotho deficiency and decreased Klotho levels in the circulation even early in stage 1 of CKD, α-Klotho serves as a sensitive biomarker for renal insufficiency and also a novel predictor of risk of overall mortality of CVD events in CKD. Meanwhile, loss of Klotho resulted from kidney dysfunction markedly contributes to the progressive development of CKD and CVD. By contrast, prevention of Klotho decline using exogenous supplementation or genetically activated ways by several mechanisms can dramatically mitigate cardiac dysfunction, prevent vascular calcification, and retard the progression of CKD-accelerated atherosclerosis. Key Messages: Klotho deficiency is proposed as a novel predictive biomarker as well as a pathogenic contributor to CVD events in CKD. In the future, Klotho may be a crucial potential therapeutic strategy to decrease the burden of CVD comorbidity with CKD in clinics.